Stock Prices and Monetary Policy: An Impulse Response Analysis - Caporale, Guglielmo Maria; Soliman, Alaa M. (International Journal of Economics and Financial Issues, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--> This paper analyses the relationship between monetary policy and the stock market with the aim of gaining new insights into the transmission mechanism of monetary policy. The empirical findings shed light on the importance of stock prices for money demand and therefore provide useful information to monetary authorities to decide on policy actions. A technique developed by Wickens and Motto (2001) for identifying shocks by estimating a VECM for the endogenous variables is employed. The reported evidence suggests that stock markets play a significant role in the money demand function. Keywords: Asset Prices; Stock Market; Monetary Policy; Impulse Response Analysis; VECM; VAR JEL Classifications: E41; E52 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> <!--[if gte mso 9]> 800x600 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->